HOPE PADAWANITA YANG MENGIKUTI PROGRAM BAYI TABUNG (STUDI PERBEDAAN ANTARA PASIEN BARU DAN PASIEN BERULANG) - Sandra Handayani Sutanto (Psycho Idea, 2018)
One of married couple's expectancies is to have offspring. But not all the couples get the offspring due to infertility problems. This infertility problem could be solved by doing in-vitro-fertilization (IVF) programme, but nevertheless the success probability using this IVF method is 50-70%. To support the IVF programme, the patients need physical, mental, financial preparation and hope. Hope becomes one of the supports to make the program successful, because when the patients have hope, the patients also have goal and find alternative ways to make the program successful. Hope is also affected by previous successes, so it's possible to have differences hope between new patients and recurring patients-who have failed in the programme. This research formula is to find out hope differences of new patients and recurring patients. The purpose of this research is to acknowledge hope differences of new patients and recurring patients. Subject of this research is divided between two groups, the new patients and recurring patients. Characteristic of the participant are women, married, don’t have any children or plan to add children, and on going in-vitro fertilization programme.This research method is based on quantitative approach and using purposive sampling.Data collection are taken in Indonesian Reproductive Science Institute by giving Hope Adult Scale that consist 9 items, which represent willpower and waypower. Demographic data are required, consist of age, occupation, education, age of marriage, ethnic and consultation to psychologist. The result of this research shows difference hope between new patients and recurring patients, which recurring patients have greater hope than the new one. The willpower dimension of recurring patients also higher than new patients. It shows that they will to have offspring are bigger than new patients.Key words : Infertility, IVF Patients, Hope